Using cloud platforms to build distributed learning management systems - Sokol, Volodymyr Yevhenovych; Sapronov, Pavlo Yuriiovych; Bilova, Mariia Oleksiivna (Національний технічний університет "Харківський політехнічний інститут", 2020)
Distributed systems have problems with downtime, data loss during malfunctions, scalability and efficient use of computing resources. At the same time in the learning and training process, the use of a distributed system has the advantage of data processing: storage of information about students, construction of training courses, verification of passed material, etc. The problems of scaling and efficient use of resources in distributed learning management systems are investigated in this research. Cloud platforms for hosting the system, such as Amazon Web Services, Microsoft Azure, Google Cloud Platform and DigitalOcean are reviewed. Problems and features of a scalability in cloud computing are discussed. Methods, scaling and load balancing algorithms for the efficient use of computing resources are proposed. According to the list of advantages, the DigitalOcean platform was selected for the investigation. DigitalOcean provides cloud servers that can be used for quick creation of the new virtual machines for the projects. These servers allow to fully control the web hosting environment at the same time that the user pays only for the resources used. The main goal of DigitalOcean is to use a solid-state drive (SSD) to create a user-friendly platform that will allow clients to migrate projects to and from the cloud, increasing productivity with high speed and efficiency. As a result of analyzing information on existing technologies, approaches and methods for using cloud platforms in distributed systems, they have been applied to develop a solution to reduce downtime for a distributed adaptive Learning Management System (LMS). It is concluded that the use of cloud platforms for the construction of distributed LMS a practice that allows to use only the required amount of computing capacity. It is proven, that the implementation of the proposed solution into the work of adaptive LMS will improve its efficiency by reducing the time of the content delivering.

Розподілені системи мають проблеми з простоєм, втратою даних під час несправностей, масштабованістю та ефективним використанням обчислювальних ресурсів. Водночас у процесі навчання та тренінгу використання розподіленої системи має перевагу обробки даних: зберігання інформації про студентів, побудова навчальних курсів, перевірка зданого матеріалу тощо. У даній роботі досліджено проблеми масштабування та ефективного використання ресурсів в розподілених системах управління навчанням. Розглянуто хмарні платформи для розміщення системи, такі як Amazon Web Services, Microsoft Azure, Google Cloud Platform та DigitalOcean. Розглянуто проблеми та особливості масштабованості хмарних обчислень. Запропоновано методи, алгоритми масштабування та балансування навантаження для ефективного використання обчислювальних ресурсів. Відповідно до переліку переваг, для дослідження було обрано платформу DigitalOcean. DigitalOcean надає хмарні сервери, які можна використовувати для швидкого створення нових віртуальних машин для проектів. Ці сервери дозволяють повністю контролювати середовище веб-хостингу, при цьому користувач платить лише за використані ресурси. Основною метою DigitalOcean є використання твердотільного накопичувача (SSD) для створення зручної платформи, яка дозволить клієнтам перемішувати проекти в хмару та з неї, підвищуючи продуктивність з високою швидкістю та ефективністю. В результаті аналізу інформації про існуючі технології, підходи та методи використання хмарних платформ у розподілених системах було розроблено рішення щодо скорочення простоїв розподіленої адаптивної системи управління навчанням (LMS). Зроблено висновок про те, що використання хмарних платформ для побудови розподілених LMS – це практика, яка дозволяє використовувати лише необхідну кількість обчислювальних потужностей. Доведено, що впровадження запропонованого рішення в роботу адаптивної LMS підвищить її ефективність за рахунок скорочення часу доставки контенту.
Використання хмарних платформ для побудови розподілених систем управління навчанням
Keywords: virtualization; containerization; віртуалізація; контейнеризація